Pengungkapan Kinerja Lingkungan Sebagai Mekanisme Peningkatan Kinerja untuk Menciptakan Nilai Perusahaan - Fatimah Zahara (Owner : Riset dan Jurnal Akuntansi, 2022)
One of the influential factors in creating the value of a company is the disclosure of the company's environmental performance and financial performance. This study aims to analyze the effect of environmental performance disclosure to improve company performance in creating firm value. The population of this study are companies that are members of the Indonesian Sharia Stock Index (ISSI) from 2017 to 2021. The sample of this study was selected by purposive sampling method from companies listed on the Indonesian Sharia Stock Index (ISSI) in 2017-2021, so that the selected 17 companies that meet the criteria in the sample in this study. This research uses index scores from several checklist items related to the disclosure of carbon gas emissions to measure environmental performance. As for the financial performance variable, the researcher uses the financial ratio indicator, namely the profitability ratio (ROA) and for the firm value variable, the researcher uses the Tobin's Q formula. The researcher uses the path analysis method to analyze the effect of environmental performance in creating firm value which is mediated by the firm's performance variable. Based on the results of statistical tests, the results obtained that the disclosure of carbon gas emissions can improve company performance, especially financial performance, and company performance can increase company value as well. However, company performance does not mediate the effect of disclosure of carbon gas emissions on firm value. Keywords: Disclosure of Carbon Gas Emissions, ROA, Tobin's Q